Social Studies Learning Using Audio Visual Media in Elementary School - Alfi Khairil Huda; Maria Montessori (International Journal of Educational Dynamics, 2019)
This study aims to describe an increase in student learning outcomes in social studies learning using Audio Visual media in grade IV SDN 04 Bukit Apit Puhun Bukittinggi. The type of research is PTK using qualitative and quantitative approaches. RPP assessment cycle I is 81.5% increased to 94% in cycle II, implementation of teacher action cycle I is 79% increased to 91% in cycle II, implementation of student action cycle I is 79% increased to 91% in cycle II, and Student learning outcomes in cycle I were 68.4%, increasing to 80.7% in cycle II. Thus Audio Visual media can improve student learning outcomes in social studies learning in class IV SDN 04 Bukit Apit Puhun Bukittinggi